Pattern of burden cancer breast and relationshipin to human development index in Iran 2009 to 2019: an observational study based on the Global Burden of Diseases - Fazlollah Fathollahi Shoorabeh; Elham Goodarzi; Fateme Shafeai; Sajjad Rahimi Pordanjani; Mahshid Abbasi (BMC, 2024)
Abstract Objective Breast cancer is one of the most common cancers in women worldwide. This study aims is to investigate the burden of breast cancer in Iran and its relationship with the Human Development Index (HDI) during 2009 to 2019. Study design The present study is an observational study in Iran during the years 2009 to 2019. Data related to the incidence, mortality, Years of Life with Disability (YLD), Years of Life Lost (YLL) and Disability-Adjusted Life-Years (DALY) of breast cancer in Iran were extracted from the Global Burden of Disease 2019 (GBD-2019) website. Correlation tests are used to check the relationship between these indicators and the human development index. Results The highest incidence rate of breast cancer in 2019 is related to the provinces of Gilan (29 per 100,000) and Tehran (28.55 per 100,000) and the highest rate of death from breast cancer is related to the provinces of Gilan (10.71 per 100,000). and Semnan (9.97 in 100,000). The results showed that there is a positive and significant correlation between DALY (r = 0.626, P < 0.0001), YLL (r = 0.611, P < 0.0001) and, YLD (r = 0.773, P < 0.0001) breast cancer with HDI index. There is a positive and significant correlation between the incidence (r = 0.794, P < 0.0001) and mortality (r = 0.503, P = 0.003) of breast cancer with the HDI index. Conclusions Considering that a positive correlation was observed between the incidence and burden of breast cancer and the human development index in the country, it is suggested to implement preventive measures such as public education programs to reduce the incidence and burden of breast cancer and the necessity of screening programs in areas with low human development index. It confirms the diagnosis of disease cases.